Recurrence of Dysplastic Nevi Is Strongly Associated with Extension of the Lesions to the Lateral Margins and into the Deep Margins through the Hair Follicles in the Original Shave Removal Specimens - Amin Maghari (Dermatology Research and Practice)
Melanocytic nevi, including dysplastic or atypical nevi (DN), can recur or persist following shave removal procedures, and recurrence may resemble melanoma, both clinically and histologically (pseudomelanoma). Recurrence may originate from proliferation of the remaining neoplastic melanocytes following incomplete removal. The present study determines the rate and etiology of this event. A cross-sectional analysis of 110 excision specimens showing histological recurrence was performed, and these specimens were compared to the slides of the original shave specimens showing mildly atypical DN. In the second portion of the study, a retrospective review of 167 cases with biopsy-proven mildly atypical DN which were followed up for at least two years was conducted to determine the rate of recurrence/persistence. When followed up for two years, DN, with positive shave margins, defined by extension or very close extension (≤0.2 mm) of the lesions to the lateral margins and into the deep margins through the hair follicles in the shave removal specimens, have a higher probability of recurrence than DN with negative (or clear) margins (odds ratio (OR) = 158; 95% confidence interval (CI) = 36.62–683; P<0.001). The overall rate of histologically confirmed recurrence/persistence was approximately 10%.